Quality of service management and optimal planning for wireless multimedia sensor networks (2015)
"A WMSN (Wireless Multimedia Sensor Network) consists of a sent of embedded processing units, called sensors communicating via wireless links, whose main function is la collection of parameters related to the surrounding environment. There are many problems to resolve to this kind of networks. In this thesis, we are interested in the following aspects: routing of heterogeneous data (scalar and multimedia) from the nodes of a WMSN to the sink in order to provide better QoS experience to users; and a optimized deployment of directional sensors of a WMSN in a three-dimensional surface with the objective to cover all the control points as defined in such a space.Overall, the proposed solutions in this thesis are both innovative and practical."--Tomado del Formato de Documento de Grado.